Associating Liver Partition and Portal Vein Ligation for Staged Hepatectomy for Unresectable Hepatitis B Virus-related Hepatocellular Carcinoma: A Single Center Study of 45 Patients. Issue 3 (March 2020) - Wang, Zheng; Peng, Yuanfei; Hu, Jingwu; Wang, Xiaoying; Sun, Huichuan; Sun, Jian; Shi, Yinghong; Xiao, Yongsheng; Ding, Zhenbing; Yang, Xinrong; Tang, Min; Tang, Zhaoyou; et al.
Abstract : Objective: The aim of the study is to assess the efficacy and safety of associating liver partition and portal vein ligation for staged hepatectomy (ALPPS) in patients with hepatitis B virus-related hepatocellular carcinoma (HCC). Background: ALPSS allows curative resection of conventionally-unresectable liver tumors. However, its role in HCC is largely unknown. Methods: Consecutive HCC patients who underwent ALPPS at our center between April 2013 and September 2017 were retrospectively studied. The oncological results were compared with patients receiving transcatheter arterial chemoembolization (TACE), and patients undergoing one-stage resection by using propensity score matching (PSM) analysis. Results: The median tumor diameter was 13 cm (range: 6–22 cm) in patients with a single tumor (n = 28), whereas the median total tumor diameter was 12 cm (range: 9–31 cm) in patients with multiple tumors (n = 17). After stage-1 ALPPS, the median future liver remnant (FLR) increased by 56.8%. The stage-2 ALPPS was completed in 41 patients (91.1%) after a median of 12 days. The 90-day mortality rate was 11.1% (5/45). The overall survival (OS) rates at 1- and 3-year were 64.2% and 60.2%, whereas the disease-free survival (DFS) rates at 1 and 3 years were 47.6% and 43.9%, respectively. On PSM analysis, the long-term survival of patients undergoing ALPPS was significantly better than those receiving TACE (OS, P = 0.004; DFS, P < 0.0001) and similar to those subjected to one-stage liver resection (OS, P = 0.514; DFS, P = 0.849). Conclusions: The long-term survival after ALPPS was significantly better than TACE, and similar to those after one-stage liver resection. ALPPS is a viable treatment option for patients with unresectable HCC in selected patients. Abstract : Supplemental Digital Content is available in the text